The role of motivation in weight reduction programs for children and adolescents with overweight or obesity: a systematic review - Anne Herschbach; Annalena Wels; Pauline Dieckmann; Rebecca Erschens; Florian Junne; Stefan Ehehalt; Stephan Zipfel; Katrin Elisabeth Giel; Katrin Ziser (Eating and Weight Disorders)
Abstract Purpose Obesity and overweight in children and adolescents are a growing concern. Treatments should be multidisciplinary, address the whole family and contain aspects of motivation. Motivation is a well-known impact factor in medical treatment but its role in the treatment of pediatric obesity is not clear. This systematic review aims to analyze the role of motivation by summarizing theoretical frameworks and synthesizing effects of weight reduction programs that assessed motivation as either outcome or predictor. Methods This systematic review was conducted according to PRISMA guidelines. Four databases (PubMed, Web of Science, PsycINFO, Cochrane) were searched, findings were screened by two authors and assessed according to pre-determined criteria. Risk of bias was assessed with the Quality Assessment Tool for Quantitative Studies by the Effective Public Health Practice Project. Results 1899 studies were found, whereof 32 were included. The most commonly used theoretical frameworks were the Transtheoretical Model and Self-Determination Theory. In 18 of the included studies, motivation was assessed as outcome. In most of them, motivation increased towards the end of the weight reduction program. 15 studies used motivation to predict different outcome variables, however, with no conclusive evidence on the predictive power of motivation on different outcomes. Conclusion Motivation can be enhanced over the course of a weight reduction program, mainly in pediatric patients. The predictive power of motivation on different outcomes is still not clear due to the heterogeneity of included studies. More research is needed to implement the current findings in future pediatric weight reduction programs. Level of evidence: Level 1, systematic review.